Fractures reduction with osteoporotic treatments in patients over 75-year-old: A systematic review and meta-analysis - Guillaumin, Michel; Poirson, Bastien; Gerazime, Aurélie; Puyraveau, Marc; Tannou, Thomas; Mauny, Fréderic; Toussirot, Éric (Frontiers in Aging, 2022)
Background: Osteoporosis consists in the reduction of bone mineral density and increased risk of fracture. Age is a risk factor for osteoporosis. Although many treatments are available for osteoporosis, there is limited data regarding their efficacy in older people. Objective: To evaluate the efficacy of osteoporosis treatments in patients over 75 years old. Methods: We reviewed all published studies in MEDLINE, Cochrane and EMBASE including patients over 75 years old, treated by osteoporosis drugs, and focused on vertebral fractures or hip fractures. Results: We identified 4393 records for review; 4216 were excluded after title/abstract review. After full text review, 19 records were included in the systematic review. Most studies showed a reduction in vertebral fracture with osteoporosis treatments, but non-significant results were observed for hip fractures. Meta-analysis of 10 studies showed that lack of treatment was significantly associated with an increased risk of vertebral fractures at one (OR=3.67; 95%CI=2.50-5.38) and three years (OR=2.19; 95%CI= 1.44-3.34), and for hip fractures at one (OR=2.14; 95%CI=1.09-4.22) and three years (OR=1.31, 95%CI=1.12-1.53). Conclusion: Osteoporosis treatments are shown to be effective in reducing the risk of hip and vertebral fractures in older people. However, most of the data derived from post hoc and preplanned analyses or observational studies.